The effect of parental psychological control on children’s peer interactions in China: the moderating role of teachers’ emotional support - Chen, Ronghui; Li, Shujuan; He, Siying; Yan, Jin (Frontiers in Psychology, 2024)
Peer interactions are critical to young children's social development, and proximal-system has a direct influence on personal growth. The study aims to analyze the relationship between parental psychological control and young children's peer interactions, as well as the moderating role of teachers' emotional support in this association. A total of 241 children aged 3-6 years, alongside their parents, and 27 teachers, participated in the study. Teachers reported children's peer interactions whilst parents reported their psychological control. The level of teachers' emotional support was co-coded by two researchers. The results of the study indicated that parental psychological control was significantly and negatively related to young children's peer interactions; teachers' emotional support was significantly and positively related to young children's peer interactions; the cross-level moderating effect validates our hypothesis that teachers' emotional support has a moderating effect between parental psychological control and young children's peer interactions, buffering the impact of parental psychological control on young children's peer interactions. These findings expand our comprehension of the association between parental psychological control, teachers' emotional support, and young children's peer interactions, and provide guidance for integrating the components of the proximal system and devising interventions to establish a home-school harmony environment that fosters children's social development. KEYWORDS psychological control, peer interactions,young children, teacher support, China